IDENTIFIKASI KAWASAN PESISIR PEMUTERAN SEBAGAI KAWASAN KONSERVASI LAUT - Widiani, Desak Made Sukma (Jurnal Anala, 2017)
Buleleng regency is one of nine districts and town in the province of Bali. Buleleng regency marine area is the largest marine area between the others, with a 144 km long coastline. Pemuteran beach is one of the beach which is visited by many tourists in North Bali. Pemuteran has the largest area of shallow coral reefs in Bali that is easy to enjoy its beauty. Pemuteran is also famous as an area with a high passion for marine conservation projects artifisal Biorock coral reef in the world. Behind all of the potential possessed by Pemuteran beach, there are also many problems faced in this coastal region. Marine ornamental fishing effort, and cultured corals often be pros and cons, because still found some fishermen who use potassium cyanide to catch fish, and the extraction of natural coral for export. The purpose of this research was to identify the condition of the coastal area of Pemuteran, the potentials, and the problems faced today in coastal zone management of Pemuteran. In addition, identification of threats that will occur in the future need to be given special attention, it can be used as a reference for the management of coastal areas in the future for the relevant government, indigenous villages, investors, and local communities so that development in coastal Pemuteran thrive well without damaging the environment or marine ecosystems. Â  Key word: coastal, pemuteran village, reef, conservation.